Permainan Edukasi Labirin Virtual Reality Dengan Metode Collision Detection Dan Stereoscopic - Sang, Aditya Bhaskara Gde; Buana, Putu Wira; Purnawan, I Ketut Adi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 2 Agustus 2017, 2017)
General knowledge is the knowledge most people know about. LIPI (Indonesian Institute of Sciences) Survey’s in 2015 states 54% of 1,829 respondents are less aware of knowledge and technology information. Most Indonesians prefer using internet for social media rather than seeking information about knowledge or issues in society [1] . This problem can be overcome with more interactive educational media, so can add insight of general knowledge in fun way. Virtual Reality is technology capable of creating interactive virtual environment. Virtual Reality is used to create educational game called LabirinVR. LabirinVR created using GoogleVR SDK with Collision Detection and Stereoscopic Vision Methods. Game interactions utilize Accelerometer and Gyroscope sensors. The application is able to increase the ability of thinking, creativity, and insight of general knowledge of Indonesia and the world. The application function test result is 100% valid and has 98% feasibility level, so it has good UAT (User Acceptence Test) [2] , accepted and used by the people.